Systematic Literature Review (SLR): Optimizing the Potential of Sharia Tourism in Indonesia to Improve Competitiveness and Local Economic Prosperity - Yogi Oriena Pasaribu; Zuhrinal M Nawawi; Rahmi Syahriza (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Sharia tourism is one of the sectors that has great potential in supporting economic growth and the welfare of local communities in Indonesia. Considering that Indonesia is the country with the largest Muslim majority population in the world, optimizing the potential of sharia tourism can be an important strategy to attract domestic and international tourists who are looking for a tourism experience that is in accordance with Islamic principles. This study aims to identify various challenges and solutions needed in optimizing the potential of sharia tourism in Indonesia through the Systematic Literature Review (SLR) approach. This study is based on 13 research journals published between 2018 and 2023. The results of the analysis show that low competitiveness, lack of infrastructure, and limited understanding of the concept of sharia tourism are the main obstacles in the development of this sector. The proposed solutions include the development of supporting infrastructure, education of industry players about sharia principles, innovation in halal tourism products, and synergy between the government, industry players, and local communities. Optimizing sharia tourism in Indonesia is expected to improve local economic welfare by creating jobs and encouraging the growth of sharia-based MSMEs.